2003
DOI: 10.1016/s0378-1097(03)00749-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of β-decarboxylase activities inStaphylococcus carnosus833, a strain used in sausage fermentation

Abstract: In sausage, Staphylococcus carnosus increases the levels of methyl ketones which could arise from incomplete L-oxidation of fatty acids followed by a decarboxylation. The objective of this work was to characterize the L-decarboxylase activities in cell-free extract. By using different substrates, at least two kinds of L-decarboxylase activities were shown: an acetoacetate-like and an oxaloacetate-like. The first one leads to the production of ketones from ethylbutyryl acetate or acetoacetic acid. The activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Production from hexanoylcarnitine probably occurred as a result of hydrolysis to hexanoic acid, since this ester is not an intermediate in the β -oxidation pathway. Decarboxylation of EOH to 2-pentanone was evidence of β -ketoacyl decarboxylase [20, 21] required for the final step of the proposed pathway. Like others, we found that methylketone production is apparently limited to one cycle of the β -oxidation pathway [11, 12], since octanoic acid was only chain-shortened by one carbon unit to 2-heptanone and did not generate 2-pentanone.…”
Section: Resultsmentioning
confidence: 99%
“…Production from hexanoylcarnitine probably occurred as a result of hydrolysis to hexanoic acid, since this ester is not an intermediate in the β -oxidation pathway. Decarboxylation of EOH to 2-pentanone was evidence of β -ketoacyl decarboxylase [20, 21] required for the final step of the proposed pathway. Like others, we found that methylketone production is apparently limited to one cycle of the β -oxidation pathway [11, 12], since octanoic acid was only chain-shortened by one carbon unit to 2-heptanone and did not generate 2-pentanone.…”
Section: Resultsmentioning
confidence: 99%
“…Among these metabolites, nitrate reductase, catalase, and superoxide dismutase not only promote the formation of nitrosomyoglobin to stabilize the color of products but also reduce the fat oxidation of products (Greppi et al., 2015; Mhamdi et al., 2017). Some studies (Fadda et al., 2002; Fadda et al., 2003) showed that sausage fermentation with S. carnosus 833 had more methyl ketones that contributed to the cured aroma of the sausage. This may be caused by the decarboxylase secreted by S. carnosus 833 during fermentation.…”
Section: Introductionmentioning
confidence: 99%